(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The usage of automobiles is rising nowadays days and people, resulting in more pollution, traffic jams, and parking space difficulties, with finding a free parking spot becoming increasingly challenging. A Verilog HDL-based system for safe automotive parking management is proposed in this research. This machine is made up of three main parts. To begin, locate the vacant slot and determine the distances. Second, book the appointment in online mode. The entering and exit of passwords are addressed. Safety measures number three. Our execution time is drastically reduced when we use FPGA. This project is about building a software that simplifies the process of finding available parking spots and monitoring of parked cars in a parking lot. Due to the huge increase in availability and utilisation of parking spaces, finding an empty spot has become significantly more difficult. In recent years, there has been an increase in the number of automobiles. As the number of automobiles on the road grows, traffic congestion and pollutants increase (noise and air pollution). An FPGA based parking system has been developed to overcome this issue. This article uses terminology like empty parking, Verilog HDL, traffic congestion, and vehicles.